Properties of Water Hyacinth Fibers (Eichhornia Crassipes) Filled Low Density Polyethylene/Acrylonitrile Butadiene Styrene Composites / Ahmed Saleem Oleiwi Al-Khuzaie. - Ahmed Saleem Oleiwi Al-khuzaie (School of Materials Engineering, Universiti Malaysia Perlis, 2009)
In this research, the water hyacinth fibers have been used as reinforcing components for low density polyethylene (LDPE) and acrylonittile butadiene styrene (ABS).